A releitura da apokatástasis na teologia contemporânea a partir do pensamento de Andrés Torres Queiruga - Rocha, Edevaldo (2019)
The doctrine of apokatastasis is a theme of patristic theology that is present in today's theological debates. Origins of Alexandria, man of extreme erudition, is considered the great protagonist in the development on the concept of Apokatástasis due to a resignification for its history. The object of this dissertation is an apokatastasis, a concept that is a common language of antiquity, especially in the Greek world, in the profane, philosophical and theological environments. This polysemy about apokatástasis is relevant in an analysis in any environment in a text, especially between some Padron’s of the world communicating to message salvific in the language, which context in the species (sec. III), philosopher and exegete that has the pastoral intention of communicating a Christian message according to the orthodoxy of his community, especially among the intellectuals who appear as arguments of the Gnostic currents of the time. This is found in the fundamental of a relegation of apokatastasis, by be linked to the practice of faith, that is, theology and life of hands given, a situation that is alive in the contemporary conveillance along the concordance of the Vatican Council II. A theology of Andrés Torres de Queiruga corresponds to a proposal from below, embodied. This is the point of the fundamental the dialogue of a plural society and moved by the religious critic. The itinerary for this rereading pervades the dialectics of a God who is love and an autonomy of creation, since the presuppositions of the original theology. This itinerary between the vocabulary of apokatastasis origeniana to the Queiruguiana, enchanting, the identifier continuous, and the software monitoring, that always the updates of the human monitoring. Whether it is in the historical or transcendent scope, evidently without rejecting human freedom, being able to mark a theology that is faced with the postmodern world, it may be through hope in Christ that a human being is fully realized in overcoming evil and, thereby exposing universal so dear to God